2020
DOI: 10.5005/jp-journals-10054-0166
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Homocysteine Level Variations in Sickle Cell Disease: A Meta-analysis Study

Abstract: Background: Serum homocysteine levels have been observed to be increased in sickle cell disease (SCD). The biological mechanism of synthesis and regulation of the homocysteine remains unclear. This meta-analysis aims to provide an overview of the serum homocysteine level changes and to discuss its significance in SCD. Materials and methods: This meta-analysis is to determine serum homocysteine level changes during SCD and was conducted under the PRISMA guidelines. Without language restrictions, the articles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…On the other hand, a decade-old meta-analysis revealed that malnutrition and under-nutrition are common in SCD children from the Middle East, possibly a consequence of the poor knowledge of the nutritional status of Arab paediatric patients [ 59 ]; this reflects in micro and macro nutritional deficiencies leading to greater disease severity and poorer quality of life, a situation not dissimilar from adult Arab SCD patients [ 60 ]. A previous meta-analysis on the relation between HC and SCD concluded that plasma HC could be considered a bio-marker of SCD as the calculated effect size favoured SCD, but the authors investigated neither the source of the heterogeneity nor performed any subgroup analysis, leaving their results unsupported and open to criticism [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a decade-old meta-analysis revealed that malnutrition and under-nutrition are common in SCD children from the Middle East, possibly a consequence of the poor knowledge of the nutritional status of Arab paediatric patients [ 59 ]; this reflects in micro and macro nutritional deficiencies leading to greater disease severity and poorer quality of life, a situation not dissimilar from adult Arab SCD patients [ 60 ]. A previous meta-analysis on the relation between HC and SCD concluded that plasma HC could be considered a bio-marker of SCD as the calculated effect size favoured SCD, but the authors investigated neither the source of the heterogeneity nor performed any subgroup analysis, leaving their results unsupported and open to criticism [ 61 ].…”
Section: Discussionmentioning
confidence: 99%